2006
DOI: 10.1152/japplphysiol.00361.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in normobaric hypoxia in endurance runners. II. Improvement of mitochondrial properties in skeletal muscle

Abstract: This study investigates whether adaptations of mitochondrial function accompany the improvement of endurance performance capacity observed in well-trained athletes after an intermittent hypoxic training program. Fifteen endurance-trained athletes performed two weekly training sessions on treadmill at the velocity associated with the second ventilatory threshold (VT2) with inspired O2 fraction = 14.5% [hypoxic group (Hyp), n = 8] or with inspired O2 fraction = 21% [normoxic group (Nor), n = 7], integrated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
78
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 54 publications
8
78
1
1
Order By: Relevance
“…Accordingly, the apparent K m to ADP (inversely proportional to the apparent affinity of mitochondria for ADP) was high in all our athletes, regardless of the magnitude of their drop in V O 2max with moderate hypoxia, suggesting that the sensitivity to cytosolic ADP is not a key factor involved in the hypoxia tolerance in athletes with already high K m values. Nevertheless, high K m values reflect a low sensitivity of mitochondrial respiration to cytosolic ADP, as expected in endurance-trained subjects (34,47,51) with skeletal muscles featuring high oxidative capacities (8,31,48,53,55,62).…”
Section: Maintenance Of V O 2max and Maximal A-vo 2 Difference In Hypmentioning
confidence: 80%
See 2 more Smart Citations
“…Accordingly, the apparent K m to ADP (inversely proportional to the apparent affinity of mitochondria for ADP) was high in all our athletes, regardless of the magnitude of their drop in V O 2max with moderate hypoxia, suggesting that the sensitivity to cytosolic ADP is not a key factor involved in the hypoxia tolerance in athletes with already high K m values. Nevertheless, high K m values reflect a low sensitivity of mitochondrial respiration to cytosolic ADP, as expected in endurance-trained subjects (34,47,51) with skeletal muscles featuring high oxidative capacities (8,31,48,53,55,62).…”
Section: Maintenance Of V O 2max and Maximal A-vo 2 Difference In Hypmentioning
confidence: 80%
“…In a previous study, we showed that V max was positively correlated to V O 2max when the population ranges from sedentary (V O 2max ϭ 28.5 ml·kg Ϫ1 ·min Ϫ1 ) to moderately trained subjects (V O 2max ϭ 50 ml·kg Ϫ1 ·min Ϫ1 ) (51). However, in subsequent studies, endurance athletes with higher V O 2max (ϳ60 ml·kg Ϫ1 ·min Ϫ1 ) were shown to have similar V max values compared with their moderately trained counterparts (12,34), suggesting that the quantitative aspects of tissue oxidative capacity levels off before the highest levels of endurance training are reached. Moreover, the higher V O 2max demonstrated by endurance-trained athletes was not accompanied by any increase in enzymatic markers of quantitative aspects of mitochondrial function (34).…”
Section: Maintenance Of V O 2max and Maximal A-vo 2 Difference In Hypmentioning
confidence: 96%
See 1 more Smart Citation
“…Adaptive responses to the respiratory tract and cardiovascular system are produced and, at the same time, the mitochondrial efficiency, pH / lactate regulation [81,164], and physical performance are increased [17, 108,143].…”
Section: Intermittent Hypoxia and Exercise: Possible Applications In mentioning
confidence: 99%
“…At a cellular level this can manifest as a low sensitivity to cytosolic ADP and an enhanced sensitivity to creatine for mitochondrial respiration in permeabilized muscle fibers (1,20). These characteristics are particularly evident in muscle from athletic humans (49) and are enhanced in humans after exercise training in hypoxia (31) and in rats that have been artificially selected for exercise endurance capacity (44). However, the ADP and creatine sensitivities of bird flight muscle are unknown, and it is conceivable that improved CK shuttling could benefit exercise performance at high altitude.…”
mentioning
confidence: 99%